The Role of Bales Nae Tradition in Strengthening Family Harmony and Social Cohesion in the Sasak Community of Lombok, Indonesia - Yazid, Afthon; Sugitanata, Arif; Hasan, Faradila; Ulirrahmi, Fauzia; Sholikhah, Siti Khamidatus (Jurnal Ilmiah Al-Syir'ah, 2024)
This research investigates the "Bales nae" tradition within the Sasak community in Lombok, Indonesia. Bales nae is an essential post-wedding ritual where the groom's family visits the bride's family following the merariq ceremonies. This tradition aims to strengthen family bonds, foster mutual respect, and preserve cultural heritage. Using a socio-legal approach and theories from Émile Durkheim and Maqashid Sharia, this qualitative study explores the reasons why the Sasak community maintains this tradition. Data were collected through observation and interviews with 12 key informants, including community members, traditional leaders, and families who have practised Bales nae. The research findings reveal that Bales nae functions to introduce and strengthen relationships among extended families, enhance social cohesion, and preserve cultural heritage. Durkheim's functionalism theory highlights the role of Bales nae in social stability and solidarity, while Maqashid Sharia emphasizes its contribution to preserving religion, life, intellect, lineage, and property. This tradition, with its rich symbolic meaning, underscores the importance of maintaining cultural practices amid modern influences. The study concludes that Bales nae is crucial for reinforcing family and social structures, reflecting the profound significance of traditional rituals within the Sasak community.